1997
DOI: 10.1002/(sici)1099-1352(199707/08)10:4<194::aid-jmr365>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The mobility of troponin C and troponin I in muscle

Abstract: In vertebrate skeletal muscle, contraction is initiated by the elevation of the intracellular Ca2+ concentration. The binding of Ca2+ to TnC induces a series of conformational changes which ultimately release the inhibition of the actomyosin ATPase activity by Tnl. In this study we have characterized the dynamic behavior of TnC and Tnl in solution, as well as in reconstituted fibers, using EPR and ST-EPR spectroscopy. Cys98 of TnC and Cys133 of Tnl were specifically labeled with malemide spin label (MSL) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Conventional EPR spectra of randomly oriented samples (myofibrils) and saturation transfer EPR experiments showed that the spin label is immobilized on the nanosecond time scale of the experiments presented below and on the millisecond time scale of the ST-EPR experiments (11,24). Thus the spectral changes which we report below are due to changes in the orientational distribution of the labeled domain at Cys98 of TnC and not due to motion of the label with respect to the protein.…”
Section: Resultssupporting
confidence: 85%
“…Conventional EPR spectra of randomly oriented samples (myofibrils) and saturation transfer EPR experiments showed that the spin label is immobilized on the nanosecond time scale of the experiments presented below and on the millisecond time scale of the ST-EPR experiments (11,24). Thus the spectral changes which we report below are due to changes in the orientational distribution of the labeled domain at Cys98 of TnC and not due to motion of the label with respect to the protein.…”
Section: Resultssupporting
confidence: 85%
“…[20][21][22][23] Although in vitro structures are available for most of the troponin components and their complexes, obtained by X-ray, NMR and FRET methods, it is important to observe dynamic interactions in the complexes in situ. Electron paramagnetic resonance (EPR) is a powerful tool for measuring the mobility of spin labels attached to a domain in a protein, [24][25][26][27][28][29][30] by determining the angle of spin label toward a magnetic field [31][32][33][34][35] and the distance between two spin labels. 36,37 The methods for exchange of TnC and myosin light chain in muscle fibres [38][39][40] have made it possible to follow the conformational changes of TnC or myosin neck in permeabilized muscle fibre systems.…”
Section: Introductionmentioning
confidence: 99%
“…InVSL has been previously found to be fully immobilized on a number of proteins, e.g., skeletal myosin S1 and ELC (27,28), RLC (29), troponin C and troponin I (41). To check the immobilization of InVSL on Cys-108 of gRLC we have cross-linked the InVSL-RLC to DITC-coated glass beads.…”
Section: Invsl As a Probe For Domain Motionmentioning
confidence: 57%